Effects of quercetin on polycystic ovary syndrome in animal models: a systematic review and meta-analysis - Pingping Su; Chao Chen; Liang Pang; Kai Wu; Yun Sun (Reproductive Biology and Endocrinology, 2024)
Abstract Background Metformin is an insulin sensitizer that is widely used for the treatment of insulin resistance in polycystic ovary syndrome patients. However, metformin can cause gastrointestinal side effects. Purpose This study showed that the effects of quercetin are comparable to those of metformin. Therefore, this study aimed to systematically evaluate the efficacy of quercetin in treating PCOS. Methods The present systematic search of the Chinese National Knowledge Infrastructure (CNKI), Wanfang Data Information Site, Chinese Scientific Journals Database (VIP), SinoMed, Web of Science, and PubMed databases was performed from inception until February 2024. The methodological quality was then assessed by SYRCLE’s risk of bias tool, and the data were analyzed by RevMan 5.3 software. Results Ten studies were included in the meta-analysis. Compared with those in the model group, quercetin in the PCOS group had significant effects on reducing fasting insulin serum (FIS) levels (P = 0.0004), fasting blood glucose (FBG) levels (P = 0.01), HOMA-IR levels (P < 0.00001), cholesterol levels (P < 0.0001), triglyceride levels (P = 0.001), testosterone (T) levels (P < 0.00001), luteinizing hormone (LH) levels (P = 0.0003), the luteinizing hormone/follicle stimulating hormone (LH/FSH) ratio (P = 0.01), vascular endothelial growth factor (VEGF) levels (P < 0.00001), malondialdehyde (MDA) levels (P = 0.03), superoxide dismutase (SOD) levels (P = 0.01) and GLUT4 mRNA expression (P < 0.00001). Conclusion This meta-analysis suggested that quercetin has positive effects on PCOS treatment. Quercetin can systematically reduce insulin, blood glucose, cholesterol, and triglyceride levels in metabolic pathways. In the endocrine pathway, quercetin can regulate the function of the pituitary-ovarian axis, reduce testosterone and luteinizing hormone (LH) levels, and lower the ratio of LH to follicle-stimulating hormone (FSH). Quercetin can regulate the expression of the GLUT4 gene and has antioxidative effects at the molecular level.